2022
DOI: 10.1080/21645515.2022.2096375
|View full text |Cite
|
Sign up to set email alerts
|

Mumps serological surveillance following 10 years of a one-dose mumps-containing-vaccine policy in Fujian Province, China

Abstract: Background Since 2008, Fujian province provided measles-rubella (MR) vaccine at 8 months followed by measles-mumps-rubella (MMR) vaccine at 18 months a one-dose mumps-containing-vaccine (MuCV) schedule. Several mumps outbreaks have occurred recently in Fujian. Serological surveillance can assess population immunity to mumps and identify risk factors for mumps. Methods We conducted a cross-sectional serosurvey of mumps IgG antibodies in the general population of Fujian P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Regarding the bimodal seasonal and age distribution of mumps, the largest infection peaks occurred in May and June, and students under 15 years of age were the most common affected group. This finding is consistent with previous studies [ 12 , 18 , 39 , 40 ]. However, a study in the Netherlands showed that mumps peaked in spring and autumn, and students aged 18–25 accounted for 67.9% of cases [ 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the bimodal seasonal and age distribution of mumps, the largest infection peaks occurred in May and June, and students under 15 years of age were the most common affected group. This finding is consistent with previous studies [ 12 , 18 , 39 , 40 ]. However, a study in the Netherlands showed that mumps peaked in spring and autumn, and students aged 18–25 accounted for 67.9% of cases [ 41 ].…”
Section: Discussionsupporting
confidence: 94%